Analysis and Measurement of Investment in The Industrial Sector and Its Impact on Unemployment in Iraq for The Period (2004-2022) - Abdul Hussein Kadim, Haitham; Saleh , Lawrence Yahiya (Journal of Economics and Administrative Sciences, 2025)
The study scrutinizes the influence that industrial investment has on unemployment rates in Iraq during the years ranging from 2004 to 2022. Employing the ARDL econometric model, the study analyzes and interprets the net as well as foreign investments and their concomitant relationship with unemployment. The findings reveal a significant and direct qualitative relationship between investment in the industrial sector and unemployment, showing that increased investment in this sector will, indeed, decrease the unemployment level. This has managed to emphasize the importance of an industrial sector in the absorption of surplus labor and contributions to gross domestic product (GDP). Further, by establishing a local industry that meets national demand of goods and services, investment in the industrial sector will have an alternative to imports and be able to stabilize the economy while improving growth. The latter includes the standpoint that efficient public spending would, therefore, be maximized by the industrial sector in terms of economic development and employment. Also, the study will emphasize how a stable investment environment can thus be used to attract local and foreign investments by having political, economic, and social stability. The results also show that bureaucracy clearing, enhancement of physical infrastructure, and legal guarantees and incentives form an important list of things that encourage a conducive investment environment. Overall, the study gives an insight to contribute better understanding on how those strategic investments in the industrial sector can serve to reduce upfront unemployment and yet foster sustainable economic growth in Iraq. This study offers significant insights to many policy makers in terms of maximizing the effectiveness of public spending and investment in achieving long-term economic objectives.